Transjugular Intrahepatic Portosystemic Shunt (TIPS) in Refractory Transudative Chylothorax due to Liver Cirrhosis. (7th February 2020) - Khaliq, Muhammad Farhan; Noorani, Muhammad Muslim; Chowdhry, Monica; Mohamed, Hesham; Koirala, Ashish
Abstract : Chylothorax is an infrequent type of pleural effusion, typically exudative, caused by obstruction or laceration of the thoracic duct by malignancy, trauma, or thoracic surgery. Transudative chylous pleural effusions are extremely rare. We report a case of a 63-year-old male with recurrent transudative chylothorax secondary to cirrhosis that completely resolved with transjugular intrahepatic portosystemic shunting (TIPS). Transudative chylous pleural effusion is an extremely rare entity with only a few cases reported in the literature to date. Transudative chylothorax can occur in patients with liver cirrhosis. Recognizing this association will prevent unnecessary testing and procedures. Timely diagnosis and early initiation of treatment are pivotal in preventing complications from malnutrition and infection by preventing loss of electrolytes, immunoglobulins, and T-lymphocytes.